Analisis Keputusan Pembelian Dengan Religiusitas Sebagai Variabel Intervening - Yasika, Regi; Maftukhatusolikhah, Maftukhatusolikhah; Sumantri, Rinol (Jurnal Iqtisaduna, 2023)
The development of increasingly modern times makes competition in the business world increasingly fierce. Every producer always carries out innovation and creativity regarding culinary products with the aim of increasing sales of their products. Lubuk Linggau City is one of the cities in South Sumatra which has diverse culinary tourism and the population is predominantly Muslim. So it is interesting to see what factors are most prioritized in the choice of purchasing products consumed by Muslim consumers. This research aims to analyze Muslim consumers’ purchasing decisions on food products in Lubuk Linggau City. This type of research is quantitative research. Data were collected through questionnaires and processed using the SmartPLS 4 statistical tool. Secondary data was obtained using questionnaires and documents taken from Muslim consumers in the city of Lubuk Linggau. The results of the research show that (1) The halal label variable has a positive effect on religiosity (2) The halal awareness variable has a positive effect on religiosity (3) The halal label variable has a positive effect on purchasing decisions (4) The halal awareness variable has a positive effect on purchasing decisions (5) The variable religiosity has a positive influence on purchasing decisions (6) Religiosity is able to mediate the positive influence of halal labels on purchasing decisions (7) Religiosity is able to mediate the positive influence of halal awareness on purchasing decisions.